SEASONAL VARIATIONS IN EGG SIZE, BROOD SIZE AND BODY LENGTH OF BOSMINA LONGIROSTRIS (CRUSTACEA: CLADOCERA) FROM LAKE IKEDA, JAPAN - Abdul Razak, Shaharudin; Saisho, Toshio (Malaysian Journal of Science, 2004)
Monthly samplings were made for 13 months at a fixed station in Lake Ikeda, a deep crater lake in order to follow the seasonal variations in egg size, brood size and body lengths of Bosmina longirostris, which is the main cladoceran species inhabiting this lake. Results of monthly samplings showed that Bosmina longirostris in summer matured at relatively small body sizes and carried smaller eggs, which produced smaller individuals. However, in autumn these individuals began to produce bigger eggs that on hatching produced relatively bigger individuals until winter. However in spring, these bigger individuals began to produce relatively smaller eggs that on hatching gave rise to smaller individuals until summer. Bigger females were able to carry more eggs than their smaller counterparts. Brood size was inversely related to egg size.